Implementasi Kebijakan Meningkatkan Literasi Generasi Muda di Kota Tangerang Selatan - Shafira Azahra; Nida Handayani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Literacy is an activity to increase knowledge. The lack of motivation of the community and the younger generation to visit the library, the lack of available reading materials, the low awareness of the importance of reading, and the lack of facilities and infrastructure provided are still problems for the government in improving literacy. The purpose of the study was to find out how Policy Implementation Improves Young Generation Literacy in South Tangerang City. The method used is descriptive with a qualitative approach. The results of this study refer to the theory of Varn Metter and Carl Varn Horn in agustino (2008: 142) which includes the following aspects: 1) Size and purpose of policy, 2) Resources, 3) Characteristics of implementing agents, 4) Attitudes or tendencies of implementers, 5) Communication between organizations and activities of implementers, 6) social, economic, and political environment. The research found that although the Library and Archives Office has shown a fairly good performance overall, there is still room for improvement because there are still some obstacles as already mentioned.